Hubungan Model Pembelajaran Discovery Learning dengan Hasil Belajar IPA Siswa Kelas Tinggi - adnan, K adnan, K; Awaluddin Muin; Sri Hasriani (Universtas Negeri Makassar, 2023)
This research is a quantitative study with a correlation design which aims to determine the relationship between the Discovery Learning Model and the Science Learning Outcomes of High Grade Students of UPT SD Inpres 6/86 Laburasseng, Libureng District, Bone Regency. The population in this study were high school students of UPT SD Inpres 6/86 Laburasseng, Libureng District, Bone Regency with 50 students. Data collection is done by using questionnaires and documentation. Data analysis technique with descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, the results of the discovery learning learning model have an average of 86,18 and a percentage of 87,77% with a very good category and the average science learning outcomes of high grade students have an average of 80,34 and a percentage of 94,23% with good category. Based on the results of inferential statistical analysis, the tcount value (3.67883) is greater (>) the ttable value (1.67722) initial significant 5%. Thus H0 is rejected and H1 is accepted. The results of the study concluded that there was a significant relationship between the Discovery Learning Model and the Science Learning Outcomes of High Grade Students of UPT SD Inpres 6/86 Laburasseng, Libureng District, Bone Regency.